(untitled) (Bangladesh Journal of Agricultural Research, 2008)
The experiment was conducted to investigate the combined effect of different plant growth regulators on growth and development of plantlets regeneration from Protocorm Like Bodies (PLBs) of hybrid orchid. The combination of BAP + NAA, BAP + IAA, BAP + IBA, and IAA + IBA at different concentrations were studied. It revealed that highest weight of PLBs (13.35g) was obtained from the combination of IAA + IBA having concentration of 1.0mg/1 each. The highest shoot height (4.530 cm) and maximum number of leaves (5.510) was obtained from 1.0 mg/1 each of BAP + NAA combination. The highest leaf length (2.573 cm) was noticed in the combination of IAA + IBA at a concentration of 1.0 mg/1 each. While the highest leaf width was obtained from 0.5 mg/1 BAP + 1.0 mg/1 IBA combination. However, for fresh weight of single shoot was maximum by the concentration 0.5 mg/1 each of BAP + IAA. The maximum number of regenerated plantlets (22.00) was obtained from 1.0 mg/each of BAP + IAA and BAP + IBA. Bangladesh J. Agril. Res. 32(4) : 629-635